ACTIVE ONE LEG STANDING EXERCISE LEBIH EFEKTIF DARIPADA CONTACTUAL HAND ORIENTATING RESPONSE (CHOR)EXERCISE UNTUK MENINGKATKAN KEMAMPUAN MOBILITAS PASIEN PASCA STROKE - Widayanto, Bambang; Pangkahila, Alex; Irfan, Muh; Ngurah, Ida Bagus; Griadhi, I Putu Adiartha; Munawarah, Mutiah (Sport and Fitness Journal; Volume 5, No.3, 2017, 2017)
Stroke is a syndrome caused by circulatory disorders of the brain (CVA) with acute onset, accompanied by clinical manifestations in the form of neurological deficit and not as a result of tumor, trauma or infection of the central nervous system. Perfomance Mobility impairment is the consequences caused by stroke. The purpose of this study was to compare a Active One Leg Standing and Contactual Hand Orientating Response (CHOR) Exercise in order to improve performance mobility instroke patients. This research used experimental methods with pre-test and post-test control group design. The number of samples per group is 7 people. Group I was gaveActive One Leg Standing Exercise, group II was gaveContactual Hand Orientating Response (CHOR) Exercise. Each group is given an exercise with an hour duration, 3 times a week for 6 weeks. Mobility perfomance measured using POMA-TinettiTest. It was concluded that Active One Leg Standing and contactual Hand orientating Response (CHOR) exercise can improve perfomance mobility in post-stroke patients. There is a significant difference in perfomance mobility level between Active One Leg Standing and contactual Hand orientating Response (CHOR) exercise.Result: (1) The result of t-test related showed mean ± SB pre test (15.57 ± 2.29) and post test (21.42 ± 2.50) with p value <0.05. (2) The result of t-test related showed mean ± SB pre test (13.85 ± 3.93) and post test (18.14 ± 3.89) with p value <0.05. (3) The result of comparation test showed the mean ± SB group I (6.85 ± 1.06) and group II (4.28 ± 0.75) with p value <0.05.